Fedir Kneiper and the creation of the girl’s private school in Chernihiv 1803-1809 - Маслійчук, Володимир (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The history of the women’s first secular educational institutions need thorough research. Details of this institution on the territory of Ukraine has preserved about Friedrich (Fedir) Kneiper’s pension in Chernihiv. In 1803 German Fedor Knejper opened pension with ambitious plans for women’s education. Despite the short time of its existence, a small number of students and the violation of the official rules about pensions, Kneiper’s institution was a successful project, which has a definite place in the history of women’s education in Ukraine. The spread of education among the women met some difficulties at different levels, but gradually became more powerful and received a new justification for its use.